A Macroeconomia do crescimento sustentado - Oreiro, José Luís da Costa; Curado, Marcelo Luiz; Escatolin, Fábio Dória; Meirelles, José Gabriel Porcile; Nakabashi, Luciano; Lemos, Breno Pascualote; Padilha, Rodrigo Ayres (Revista Economia & Tecnologia, 2007)
*